Optical coherence tomography to evaluate the interaction of different edge designs of four different silicone hydrogel lenses with the ocular surface - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2015)
Purpose: To evaluate the lens edge interaction with the ocular surface with different edge designs using optical coherence tomography and to examine the effect of lens power on the lens edge interactions. Methods: Four types of silicone hydrogel lenses with different edge designs (round-, semiround-, chisel-, and knife-edged) at six different powers (+5.0, +3.0, +1.0, -1.0, -3.0, and -5.0 diopters) were fitted to both eyes of 20 healthy volunteers. Optical coherence tomography images were taken at the corneal center and at the limbus within 15-30 minutes after insertion. The images were evaluated with respect to two parameters: conjunctival indentation exerted by the lens edge; and the tear film gaps between the posterior surface of the lens and the ocular surface. The amount of conjunctival indentation was measured with the distortion angle of the conjunctiva at the lens edge. Results: The degree of conjunctival indentation was highest with the chisel-edged design followed by the semi-round design (P<0.0001). Knife-and round-edged lenses exerted similar levels of conjunctival indentation that was significantly lower compared to chisel-edged lens (P<0.001). For each one of the tested lens edge designs, no significant difference was observed in the conjunctival indentation with respect to lens power. The chisel-edged lens produced the highest amount of conjunctival indentation for each one of the six lens powers (P<0.0001). Post-lens tear film gaps at the limbus were observed at most in the round-edge design (P=0.001). Conclusion: The fitting properties of contact lenses may be influenced by their edge design but not by their lens power.
Keywords: Acuvue Oasys; Air Optix Aqua; PremiO; PureVision 2 HD; silicone hydrogel contact lenses; POSTLENS TEAR FILM; DIURNAL-VARIATION; CONTACT-LENSES; WEAR; MOVEMENT; FIT; TOPOGRAPHY